Automated detection of superficial macrophages in atherosclerotic plaques using autofluorescence lifetime imaging. (June 2019) - Rico-Jimenez, Jose J.; Serafino, Michael J.; Shrestha, Sebina; Chen, Xi; Kim, Wihan; Adame, Jessie; Buja, L. Maximillan; Vela, Deborah; Applegate, Brian E.; Jo, Javier A.
Abstract: Background and aims: Macrophages play an important role in the development and destabilization of advanced atherosclerotic plaques. Hence, the clinical imaging of macrophage content in advanced plaques could potentially aid in identifying patients most at risk of future clinical events. The lifetime of the autofluorescence emission from atherosclerotic plaques has been correlated with lipids and macrophage accumulation in ex vivo human coronary arteries, suggesting the potential of intravascular endogenous fluorescence or autofluorescence lifetime imaging (FLIM) for macrophage imaging. The aim of this study was to quantify the accuracy of the coronary intima autofluorescence lifetime to detect superficial macrophage accumulation in atherosclerotic plaques. Methods: Endogenous FLIM imaging was performed on 80 fresh postmortem coronary segments from 23 subjects. The plaque autofluorescence lifetime at an emission spectral band of 494 ± 20.5 nm was used as a discriminatory feature to detect superficial macrophage accumulation in atherosclerotic plaques. Detection of superficial macrophage accumulation in the imaged coronary segments based on immunohistochemistry (CD68 staining) evaluation was taken as the gold standard. Receiver Operating Characteristic (ROC) curve analysis was applied to select an autofluorescence lifetime threshold value to detect superficial macrophages accumulation. Results: A threshold of 6 ns in the plaque autofluorescence lifetime at the emission spectral band of 494 ± 20.5 nm was applied to detect plaque superficial macrophages accumulation, resulting in ∼91.5% accuracy. Conclusions: This study demonstrates the capability of endogenous FLIM imaging to accurately identify superficial macrophages accumulation in human atherosclerotic plaques, a key biomarker of atherosclerotic plaque vulnerability. Graphical abstract: Image 1 Highlights: Plaque autofluorescence lifetime is correlated with superficial macrophage accumulation in coronary atherosclerotic plaques. Plaque autofluorescence lifetime can discriminate superficial macrophage accumulation in coronary atherosclerotic plaques. Intravascular fluorescence lifetime imaging has the potential for in vivo macrophage imaging of coronary atherosclerosis.